RANCANG BANGUN SISTEM MONITORING GENSET MELALUI NOTIFIKASI APLIKASI TELEGRAM - Husein Romadhoni; Gigih Priyandoko; Dedi Usman Effendy (Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2023)
Generator set (Genset) is a backup power generation system that uses kinetic energy. Generators are usually used when the PLN shutdown. To back up the electricity supply when the PLN shutdown, having a generator is very important in various industry, offices, companies and factories. Because of the importance of the need for Genset, a Genset monitoring system is needed so that generators will always ready to operation at anytime when needed. Telegram is an application that provide services to users to send messages safely and quickly. Telegram can send messages in the form of text, photos, videos and documents. Telegram is available on smartphones, tablets, and even computers, beside of being able to be used on many platforms. Based on the problems above, this research was conducted to design a Genset monitoring system that is urgently needed to support Genset operations based on the Internet of Things, there is monitoring of fuel capacity, battery voltage capacity, temperature around the Genset area which is integrated with Telegram notifications. This monitoring system can make sure that the Genset is ready to operate, and the Telegram notification will appear if one or several systems have problem, so we can take action immediately to solve the problem.